Mobilization Effects of Multilateral Development Banks - Broccolini, Chiara; Lotti, Giulia; Maffioli, Alessandro; Presbitero, Andrea (Washington, D.C. : International Monetary Fund, 2019)
We use loan-level data on syndicated lending to a large sample of developing countries between 1993 and 2017 to estimate the mobilization effects of multilateral development banks (MDBs), controlling for a large set of fixed effects. We find evidence of positive and significant direct and indirect mobilization effects of multilateral lending on the number of deals and on the total size of bank inflows. The number of lending banks and the average maturity of syndicated loans also increase after MDB lending. These effects are present not only on impact, but they last up to three years and are not offset by a decline in bond financing. There is no evidence of anticipation effects and the results are not driven by confounding factors, such as the presence of large global banks, Chinese lending and aid flows. Finally, the economic effects are sizable, suggesting that MBDs can play a vital role to mobilize private sector financing to achieve the goals of the 2030 Development Agenda.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet